Evaluation of Rumex hastatus leaves against hepatic fibrosis: a rat model - Sumaira Sahreen; Muhammad Rashid Khan; Rahmat Ali Khan (BMC, 2017)
Abstract Background Rumex hastatus leaves have been widely used as food additive and for the treatment of various liver ailments. According to our previous studies, ethyle acetate (ERL) and methanolic (MRL) fractions of R. hastatus leaves are an accessible source of natural antioxidants. In the present research work we arranged to investigate the R. hastatus leaves as hepaptoprotective agent verse hepatic damages caused by CCl4. Methods During this project we divided 48 rats into eight groups randomly. CCl4-induced damages were assessed through liver function markers viz.; alkaline phosphatase (ALP), alanine transaminase (ALT), aspartate transaminase (AST), γ-glutamyltransferase (γ-GT) and lactate dehydrogenase (LDH). Changes in lipid profile were checked by measuring serum total cholesterol (TC), triglycerides (Tg), high density lipoproteins (HDL) and low density lipoproteins (LDL). Antioxidant status was checked by the activities of antioxidant enzymes, DNA damages and cellular abnormalities at histo level. Results Administration of CCl4 in rats caused significant increase in liver function and lipid profile indicating hepatic damages which were restored by co-administration of R. hastatus extracts. Cellular and DNA damages in hepatic tissues were caused by CCl4 which shown clear hepatic fibrosis in addition to disturb antioxidant enzyme level. Co-treatment with various fractions of R. hastatus leaves regulated these markers of oxidative dysfunctions. Conclusion From the present report it was inferred that R. hastatus leaves have the ability to reverse CCl4 - induced hepatic damages.